2007
DOI: 10.1007/s11103-006-9120-0
|View full text |Cite
|
Sign up to set email alerts
|

ci21A/Asr1 expression influences glucose accumulation in potato tubers

Abstract: Asr genes are exclusively found in the genomes of higher plants. In many species, this gene family is expressed under abiotic stress conditions and during fruit ripening. The encoded proteins have nuclear localisation and consequently a transcription factor function has been suggested. Interestingly, yeast-one-hybrid experiments revealed that a grape ASR binds to the promoter of a hexose transporter gene (VvHT1). However, the role of these proteins in planta is still elusive. By using a reverse genetics approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 64 publications
5
59
3
Order By: Relevance
“…Maximum likelihood and Bayesian reconstruction methods were congruent and confirmed the previously established division of plant ASR proteins into three distinct clades corresponding to conifer, eudicot, and monocot sequences (Supplemental Fig. S1; Frankel et al, 2007). By adding all available maize sequences, we showed that within monocots, the Commelinid sequences form a monophyletic group, with Poaceae sequences falling into two distinct clades, the I-1/I-2/I-3 clade and the II-1/ II-2 clade (Supplemental Fig.…”
supporting
confidence: 77%
See 4 more Smart Citations
“…Maximum likelihood and Bayesian reconstruction methods were congruent and confirmed the previously established division of plant ASR proteins into three distinct clades corresponding to conifer, eudicot, and monocot sequences (Supplemental Fig. S1; Frankel et al, 2007). By adding all available maize sequences, we showed that within monocots, the Commelinid sequences form a monophyletic group, with Poaceae sequences falling into two distinct clades, the I-1/I-2/I-3 clade and the II-1/ II-2 clade (Supplemental Fig.…”
supporting
confidence: 77%
“…ASR overexpression studies in plants are exemplified by works carried out on Solanoideae (Kalifa et al, 2004b;Frankel et al, 2007) and Arabidopsis, although the latter does not include any ASR homologous genes (Yang et al, 2005;Liu et al, 2010). Our study demonstrated that ZmASR1-OE improved the kernel yield of transgenic maize in the field under well-watered and water-limited conditions.…”
Section: Zmasr1 Maintained Kernel Yield Under Water Deficit Conditionmentioning
confidence: 82%
See 3 more Smart Citations